The threshold effect of fasting blood glucose levels on the risk of delivering macrosomia in gestational diabetes mellitus patients - Li, Yuan; Zhu, Yumin; Zheng, Wenjun; Gao, Yumei; Huang, Ruili; Yang, Tingting; Chen, Ying (Frontiers in Endocrinology, 2025)
BackgroundGestational diabetes mellitus (GDM) is a prevalent condition during pregnancy, and macrosomia is a recognized risk associated with it. However, the specific relationship between fasting blood glucose (FBG) levels and the risk of macrosomia in GDM, particularly any potential thresholds for this relationship, remains unclear.MethodsThis retrospective cohort study analyzed data from 7,957 pregnant women who underwent antenatal care and delivered at The First People’s Hospital of Shangqiu between February 1, 2018, and December 30, 2022. Participants were stratified into three groups based on FBG levels: <5.1 mmol/L, 5.1–7 mmol/L, and ≥7 mmol/L. Multivariable logistic regression analyses were performed to assess the association between FBG levels and the risk of macrosomia. Two-piecewise regression models were applied to identify a threshold for the FBG-macrosomia relationship.ResultsThe prevalence of macrosomia increased substantially with increasing FBG levels (P < 0.001). The adjusted multivariable logistic regression analyses revealed that compared to women with FBG levels <5.1 mmol/L, those with FBG levels of 5.1–7 mmol/L and ≥7 mmol/L had 4.69 (95% CI: 4.06-5.42) and 8.65 (95% CI: 7.31-10.23) times higher risk of macrosomia, respectively (both P < 0.001). Two-piecewise regression models identified a threshold of 8.037 mmol/L. Below this threshold, each unit increase in FBG was associated with a 1.93-fold increase in the odds of macrosomia (95% CI: 1.83-2.04, P < 0.001). Above this threshold, the association was no longer statistically significant (OR = 1.04, 95% CI: 0.90-1.21, P = 0.587). Furthermore, the stratified analysis also showed a positive association between FBG level and macrosomia.ConclusionThere is a nonlinear relationship between FBG levels during pregnancy and the risk of macrosomia in GDM women, with a potential threshold effect at 8.037 mmol/L. Below the threshold, macrosomia prevalence markedly rises with elevated FBG levels, whereas above it, the association loses significance, implying a potential saturation at very high glucose levels.